The influence of product acidity and beta-glucans isolated from various sources on the mineral composition and the mechanical and microstructural properties of the femur in growing Wistar rats. (May 2018) - Aljewicz, Marek; Tonska, Elżbieta; Juskiewicz, Jerzy; Cichosz, Grażyna
Highlights: The femur parameters were influenced by the type of glucan and product acidity. The Ca content of bones depends on the pH of the product. The Ca:P ratio in the femurs of rats fed yoghurt was higher than in milk gel. Abstract: The aim of this study was to determine the influence of a standard diet enriched with yoghurt (acidified milk) and milk gel (non-acidified milk) and three structurally different beta-glucans (isolated from oats, bacteria and fungi) on the mineral composition and the mechanical and microstructural properties of the femur in growing rats. Feed intake and the feed conversion ratio were influenced by product acidity and the applied beta-glucan. A significant increase in bacterial counts was noted only in the animals fed fungal glucan. Dietary supplementation with beta-glucans significantly decreased the acidity of intestinal contents. The calcium content of bones was determined mainly by the acidity of milk gel than by the type of beta-glucans. The Ca:P ratio in the femurs of rats fed yoghurt was higher than in the animals fed milk gel. Higher failure load was noted in rats fed yoghurt with beta-glucans. Trabecular thickness was highest in rats fed yoghurt with oat beta-glucan and lowest in rats fed milk gel with fungal beta-glucan.